2008
DOI: 10.1093/rheumatology/ken024
|View full text |Cite
|
Sign up to set email alerts
|

Cod liver oil (n-3 fatty acids) as an non-steroidal anti-inflammatory drug sparing agent in rheumatoid arthritis

Abstract: This study suggests that cod liver oil supplements containing n-3 fatty acids can be used as NSAID-sparing agents in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(54 citation statements)
references
References 19 publications
0
49
0
3
Order By: Relevance
“…Fish is recommended to consume in order to reduce the risk for heart diseases (Anonymous, 2010c). In addition to reducing the risk for heart disease, regular consumption of fish can be advisable in preventing, treating, or improving a wide variety of diseases and disorders, including mental health (Mischoulon et al, 2009), chronic, systemic inflammatory disorder (Galarraga et al, 2008), dental health (Hamazaki et al, 2006) and even positive effects on different stages of cancer (Augustsson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish is recommended to consume in order to reduce the risk for heart diseases (Anonymous, 2010c). In addition to reducing the risk for heart disease, regular consumption of fish can be advisable in preventing, treating, or improving a wide variety of diseases and disorders, including mental health (Mischoulon et al, 2009), chronic, systemic inflammatory disorder (Galarraga et al, 2008), dental health (Hamazaki et al, 2006) and even positive effects on different stages of cancer (Augustsson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Fish oil may be considered as one of the richest source of n-3 PUFA among the other lipid containing foods. Therefore, it can prevent the occurrence of such diseases as depressive disorder (Mischoulon et al, 2009), cardiovascular mortality (Anderson et al, 2009), rheumatoid arthritis (Galarraga et al, 2008), tooth loss (Hamazaki et al, 2006), cardiovascular diseases (Calder, 2004), and diabetes (Woodman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Fish oils ameliorate collagen-induced arthritis, [10][11][12] and demonstrate modest effects on RA with a consistent reduction in tender joint count, morning stiffness and non-steroidal anti-inflammatory drug (NSAID) usage being observed in multiple small clinical trials when added to conventional DMARD therapy. [13][14][15][16][17][18][19][20][21][22][23][24][25] Studies suggest that higher doses of fish oil (e.g. 3-6 g/day) are more effective than lower doses.…”
Section: Introductionmentioning
confidence: 99%
“…Only one report [17] showed that glucosamine had some beneficial effects on RA symptoms. In contrast, accumulated evidence suggested that fish oil containing x-3 fatty acids [18][19][20][21] and herb oil containing c-linolenic acid [22] relieved RA symptoms to some extent. Nevertheless, patients using fish or herb oil products were fewer in number than those using products or components of cartilage.…”
Section: Discussionmentioning
confidence: 89%